Analysis of Medication Adherence, Social Support, Health Literacy, and Physical Activity on Quality of Life in Post-Kidney Transplant Patients - Andri, Febby; Jayanagara, Oscar (Green Publisher Indonesia, 2025)
This study analyzes the impact of medication adherence, social support, health literacy, and physical activity on the improvement of quality of life, mediated by patient satisfaction in post-kidney transplant patients at XYZ Hospital Jakarta. The research explores the relationships between these variables, focusing on how patient satisfaction and adherence to treatment impact Health-Related Quality of Life (HRQoL). The study employs a quantitative, analytical survey with a cross-sectional approach, involving 162 patient respondents from a census sample. Data was collected using a Likert scale-based questionnaire, and analyzed using structural equation modeling (SEM) with SmartPLS 4.0. The analysis included tests for validity, reliability, and several statistical assessments, such as collinearity, R-square, effect size, and predictive accuracy. The results indicate that four out of ten initial hypotheses were not significant, specifically regarding medication adherence. These findings highlight the importance of addressing patient compliance through improved social support and monitoring, as these factors significantly influence patient satisfaction and quality of life.